Ability to adjust nocturnal fat oxidation in response to overfeeding predicts 5‐year weight gain in adults. Issue 5 (May 2017) - Rynders, Corey A.; Bergouignan, Audrey; Kealey, Elizabeth; Bessesen, Daniel H.
Abstract : Objective: To determine whether metabolic responses to short‐term overfeeding predict longitudinal changes in body weight. Methods: Twenty‐four‐hour energy expenditure (EE) and substrate utilization were measured at baseline in a room calorimeter following 3 days of eucaloric and hypercaloric feeding (40% excess) in a sample of lean adults ( n : 34; age: 28 ± 2 y; BMI: 22 ± 3 kg/m 2 ). Body mass and fat mass (dual‐energy x‐ray absorptiometry) were measured annually for 5 years. Regression analyses examined whether changes in EE and fuel use with overfeeding predicted body weight and composition changes over 5 years. Results: Overfeeding increased EE and reduced fat oxidation when examined over the 24‐hour, waking, and nocturnal periods. Absolute change in body mass over 5 years was 3.0 ± 0.6 kg (average rate of change = 0.7 ± 0.1 kg/y, P < 0.001). Lower nocturnal (but not 24‐hour or waking) fat oxidation ( r = −0.42, P = 0.01) and EE ( r = −0.33, P = 0.05) with overfeeding were the strongest predictors of 5‐year weight gain. When adjusted for covariates, changes in nocturnal fat oxidation and EE with overfeeding predicted 41% of the variance in weight change ( P = 0.02). Conclusions: Failure to maintain fat oxidation at night following a period of overfeeding appears to be associated with a metabolic phenotype favoring weight gain.